EVALUASI KINERJA RUANG PEJALAN KAKI DI JALAN MALIOBORO YOGYAKARTA - Pradipto, Ranar; Kharis, Zulfikar; Wicaksono, Y.I.; Indriastuti, Amelia Kusuma (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Malioboro as one of most tourism destination in Yogyakarta has a large number of visitors. More than 4,000 people visiting Malioboro area per day. The number of visitors at pedestrian area resulting inability Malioboro to receive such capacity. For resolve these problems, an evaluation of the service is needed more pedestrian capacity (level of service). so that visitors will know about Malioboro growth in the future. and The reference can being recommendation as handling problems that occur at Malioboro street. The survey undertaken are pedestrian survey. Pedestrian survey is aimed to obtain number of tourists data in Malioboro pedestrians . The survey were conducted in three-point locations who can represent characters of Malioboro, in front of the Hotel Inna Garuda, Malioboro Mall and Sami Jaya. The analysis is carried out to the HCM 2000. The result of pedestrian survey are Level of Service value. Base on the parking income data the growth rate of pedestrian area is about 5.2% . in the next five years the Level of Service will be bad with Level of service D. this mean there is a crowded situation in pedestrian area. overcome these problems we need rearrangement pedestrian area along Malioboro street and make a planning analysis to resolve this issue hopefully can accommodating Malioboro area for next 5 years in Pedestrian area with Level of Service (LOS) B.